2016
DOI: 10.4137/ebo.s35909
|View full text |Cite
|
Sign up to set email alerts
|

Phi Class of Glutathione S-transferase Gene Superfamily Widely Exists in Nonplant Taxonomic Groups

Abstract: Glutathione S-transferases (GSTs) constitute a superfamily of enzymes involved in detoxification of noxious compounds and protection against oxidative damage. GST class Phi (GSTF), one of the important classes of plant GSTs, has long been considered as plant specific but was recently found in basidiomycete fungi. However, the range of nonplant taxonomic groups containing GSTFs remains unknown. In this study, the distribution and phylogenetic relationships of nonplant GSTFs were investigated. We identified GSTF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Previous phylogenetic analyses indicated that GSTFs are only found in a few restricted lineages, mostly higher plants and fungi and in some bacteria and protists . Among photosynthetic organisms, the number of genes ranges from 1 in S. moellendorffii to 38 in T. aestivum which strongly argues for the occurrence of gene duplication in a species‐specific manner .…”
Section: Discussionmentioning
confidence: 99%
“…Previous phylogenetic analyses indicated that GSTFs are only found in a few restricted lineages, mostly higher plants and fungi and in some bacteria and protists . Among photosynthetic organisms, the number of genes ranges from 1 in S. moellendorffii to 38 in T. aestivum which strongly argues for the occurrence of gene duplication in a species‐specific manner .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these classes are found among different kingdoms, such as Zeta or Theta classes whereas Lambda, Tau and DHAR classes are specific to plants. The Phi class is sometimes presented in the literature as specific to the plant kingdom but similar sequences have been identified in some fungi, bacteria, and protists (Morel et al, 2013; Munyampundu et al, 2016). Although it has some limitations, the primary sequence remains to date the most convenient criterion for classifying these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen classes have been confirmed based on phylogenetic analysis of all GSTs in eight eukaryote photosynthetic organisms, among them, eight classes are more widespread and contain tau (GSTU), phi (GSTF), lambda (GSTL), dehydroascorbate reductase (DHAR), theta (GSTT), γ-subunit of translation elongation factor (EF1G), zeta (GSTZ) and tetrachloro-hydroquinone dehalogenase (TCHQD) classes [9]. The phi and tau classes usually have more members than others in GST family, and the tau, phi, lambda and DHAR classes have long been considered as plant-specific, while the similar sequences of phi class have been discovered in some fungi and bacteria in recent years [1012].…”
Section: Introductionmentioning
confidence: 99%